DAMPAK ASEAN-INDIA FREE TRADE AREA TERHADAP EKSPOR CRUDE PALM OIL INDONESIA KE INDIA PADA TAHUN 2009-2013 - Putri, Lutfiana Ika (Transformasi, 2015)
ASEAN as a regional organization has agreed on free trade agreements with India, AIFTA in2009 and started in 2010. This study aims to explain the impact AIFTA on exports of CPOfrom Indonesia to India in the year 2009 to 2013. The research method that I use isdescriptive qualitative, which aims to determine the development and describe in detail aparticular social phenomenon, and qualitatively a certain tradition in the social sciencesWhat Knowledge is fundamentally dependent on the observations relating to the casesstudied. Source of data used are primary data and secondary data. The primary data obtaineddirectly from the informant, while the secondary data obtained through the data in the form ofrecords, documents, articles, reports or books that deal with the problems studied. Data wascollected by literature sourced from books, journals, documents, files, and websites that arevalid and interviews. As for analyzing the data, the authors used qualitative analysistechniques with three stages (1) data reduction (2) presentation of data (3) conclusion andverification. The results showed that with the ratification of the AIFTA impact on improvingIndonesia's CPO exportsto India in2009-2013. Itcan be seen thatthe presence o fintraregionalcooperationof ASEAN and India in free tradeis very helpful in increasing the exporto fCPO before AIFTA has increased now after AIFTA be increased to 5-10%. WithfacilitiesAIFTA one agreement tariffs and import dutiesin India, to further facilitate trade andIndonesian CPO exports.Key Words: AIFTA, Free Trade Area, CPO exports